Stability estimates for the inverse fractional conductivity problem - Covi, Giovanni; Railo, Jesse; Tyni, Teemu; Zimmermann, Philipp (SIAM journal on mathematical analysis, 2024)
This paper focuses on an inverse problem associated with the plate equation which is derived from models in fluid mechanics and elasticity. We establish the unique identifying results in simultaneously determining both the unknown density and the internal sources from the passive boundary measurement. The proof mainly relies on the asymptotic analysis and harmonic analysis on integral transforms.